Momentary health behaviour cues are moderated by educational attainment: findings from two ecological momentary assessment studies - Schüz, Benjamin Ernst Christoph; Wenzel, Mario; Jones, Christopher (Social science & medicine, 2025)
Socioeconomic status (SES), indicated e.g., through educational attainment substantially influences health outcomes through health behaviours. Many health behaviours such as smoking or consuming sugar-sweetened beverages (SSBs) are strongly influenced by momentary environmental and social cues in everyday life. This study examined the moderating role of SES on the relationship between such situational cues and smoking as well as SSB consumption. Data were drawn from two ecological momentary assessment studies with 46 daily smokers (Study 1) and 125 SSB consumers (Study 2) in Germany. Participants provided daily self-reports on behavioral cues and consumption over three weeks. Results revealed that lower educational attainment was associated with increased associations between situational social cues (e.g., observing others engaging in the behavior) and smoking, as well as between situational availability cues (e.g., access to SSBs) and SSB consumption. These findings suggest that individuals with lower educational attainment are both more exposed to and more susceptible to environmental cues promoting health-compromising behaviours. Addressing these disparities may require structural interventions to reduce the density and impact of such cues in disadvantaged environments.